Anti-Inflammatory Activity Test of Ethanol Extract of Ambarella Fruit Leaves (Spondias dulcis Frost) Against Male Rats Induced Carrageenan - Hasibuan, Ahmad Syukur (Indonesian Journal of Pharmaceutical Research, 2021)
In the treatment of inflammation, there are several chemical drugs, namely steroidal and non-steroidal anti-inflammatory drugs, but because they have many side effects, anti-inflammatory drugs are developed from natural ingredients, especially plants. Plants are scientifically proven to have anti-inflammatory properties, one of which is ambarella fruit leaves because it leaves contain flavonoid secondary metabolites as anti-inflammatory compounds. The objective of this study to determine the effect of giving ambarella fruit leaves on anti-inflammatory activity in male rats induced by carrageenan. The method used in this study was paw edema, namely by induction of carrageenan 0.1 ml as an irritant on the soles of the rat's feet for 360 minutes with the parameter observed was the inhibition of edema in the feet of rats using a plethysmometer. This study was an experimental study that was divided into 5 groups, namely the control group positive (diclofenac sodium 9 mg/kgBW), negative control (Na-Cmc 0.55), and three doses tested, namely 100 mg/kgBW, 300 mg/kgBW and 500 mg/kgBW. The results of this study showed a significant difference (p0.05) where flavonoid compounds from ambarella fruit leaves affect anti-inflammatory activity. The conclusion that the three doses is tested, namely 100 mg/kgBW, 300 mg/kgBW and 500 mg/kgBW has an anti-inflammatory effect where the more effective dose was 300 mg/kg kgBW.